2021
DOI: 10.3390/jcm10215066
|View full text |Cite
|
Sign up to set email alerts
|

Donor Site Morbidity in Unilateral and Bilateral Transverse Musculocutaneous Gracilis (TMG) Flap Breast Reconstruction: Sensation, Function, Aesthesis and Patient-Reported Outcomes

Abstract: The transverse musculocutaneous gracilis (TMG) flap has become a popular choice for breast reconstruction. This study aimed to compare the donor site morbidity in unilateral and bilateral procedures. Patients receiving a TMG flap (January 2008–October 2019) were invited to a follow-up and grouped according to unilateral (UL group) or bilateral (BL group) breast reconstruction. Outcome criteria included sensation, function and aesthesis of the thighs. Patient-reported outcomes were surveyed using validated ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Overall, the literature demonstrates a similarly low donor‐site morbidity of the TMG flap in comparison to other commonly used free flaps such as the DIEP‐, and profunda artery perforator (PAP) flap (Cho et al, 2020; Siegwart, Bolbos, Tapking, et al, 2021; Tomouk et al, 2017). Although the donor‐site morbidity of the TMG flap has been extensively studied, we were unable to identify studies outlining strategies for a standardized management of various donor‐site complications (Craggs et al, 2014; Siegwart, Bolbos, Haug, et al, 2021; Siegwart, Bolbos, Tapking, et al, 2021; Siegwart, Fischer, Diehm, et al, 2021). This study aims to fill this gap and provides an overview of encountered donor‐site complications, associated risk factors and their management in a large series of TMG flaps.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Overall, the literature demonstrates a similarly low donor‐site morbidity of the TMG flap in comparison to other commonly used free flaps such as the DIEP‐, and profunda artery perforator (PAP) flap (Cho et al, 2020; Siegwart, Bolbos, Tapking, et al, 2021; Tomouk et al, 2017). Although the donor‐site morbidity of the TMG flap has been extensively studied, we were unable to identify studies outlining strategies for a standardized management of various donor‐site complications (Craggs et al, 2014; Siegwart, Bolbos, Haug, et al, 2021; Siegwart, Bolbos, Tapking, et al, 2021; Siegwart, Fischer, Diehm, et al, 2021). This study aims to fill this gap and provides an overview of encountered donor‐site complications, associated risk factors and their management in a large series of TMG flaps.…”
Section: Discussionmentioning
confidence: 99%
“…However 15 of 16 patients ( 94 %) were moderately to very happy with the scar position, despite the scar being visible while wearing underwear in 12 patients ( 78 %). In their series of 59 TMG flap donor‐site scars Siegwart et al describe the necessity of scar correction in six patients ( 10.1 %) and dog ear excisions in 5 ( 8.4 %) patients (Siegwart, Bolbos, Haug, et al, 2021). Pülzl et al (2011) reported on one patient who adapted her sporting activities because of traction on the donor‐site scar and explained that sports requiring stretching of the legs can pose problems.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The TMG flap is appreciated for its reliable anatomy, convenient surgical procedure, low donor site morbidity, and the appealing look of the reconstructed breast [ 8 , 9 ]. However, harvesting the TMG flap, including a horizontal soft tissue island and part of the gracilis muscle, creates an extensive wound on the medial thigh.…”
Section: Introductionmentioning
confidence: 99%